Lot Streaming Permutation Flow Shop With Energy Awareness - D’Amico, Florencia; Rossit, Daniel Alejandro; Frutos, Mariano (International Journal of Industrial Engineering and Management, 2021)
In this work, the flow shop scheduling problem with energy awareness is approached with lot-streaming strategies. Energy consumption is modeled within the objective function, together with the makespan, by means of a normalized and weighted sum. Thus, reducing energy consumption guides the optimization process. For lot streaming approaches mathematical models are provided and assessed. The results showed that lot-streaming is an efficient strategy to address this problem, allowing to improve both makespan and total energy consumption compared to the problem without lot-streaming. In turn, the selection of processing speeds for each sublot was incorporated, which improved the strategy yielding the best quality solutions. Article history: Received (September 08, 2020); Revised (January 7, 2021); Accepted (January 11, 2021); Published online (February 03, 2021)